Signs of War: From Patriotism to Dissent - Obajtek-Kirkwood, A. author. aut Link
X, 276 p. 10 illus.
Keywords: An analysis of Vietnam, 9/11 and the Iraq War from patriotism to dissent through various visual and written signs among which the US flag, ribbons, car-stickers, cartoons, movies, the media and presidential war rhetoric.